ESTIMATING FACULTY AND STUDENT WORKLOAD FOR INTERACTION IN ONLINE GRADUATE MUSIC COURSES - McLain, Barbara Payne (Online Learning, 2005)
Research suggests that faculty perceive greater workload for online teaching. These perceptions have little quantitative support. This study utilized seven online graduate courses, over a three year period to estimate faculty and student workload for interaction via online discussions and electronic mail using average reading and typing speeds. Weekly faculty workload estimates for interaction did not exceed normal expectations for faculty “office hours” for six of the seven courses. Perceptions of excessive workload for communication may be better explained by the dynamics of online interaction found in this study. Online students attempted to contact their instructors, twenty-four hours per day, seven days per week, at least every fourteen hours. Further research is needed to establish the time needed for FTF teaching interaction and to validate actual typing and reading speeds for more accurate estimates of the time needed for online course interaction.